2012
DOI: 10.1051/0004-6361/201118718
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of dust and water ice in comet 9P/Tempel 1 fromSpitzerobservations of the Deep Impact event

Abstract: Context. The Spitzer spacecraft monitored the Deep Impact event on 2005 July 4 providing unique infrared spectrophotometric data that enabled exploration of comet 9P/Tempel 1's activity and coma properties prior to and after the collision of the impactor. Aims. The time series of spectra take with the Spitzer Infrared Spectrograph (IRS) show fluorescence emission of the H 2 O ν 2 band at 6.4 μm superimposed on the dust thermal continuum. These data provide constraints on the properties of the dust ejecta cloud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 53 publications
(88 reference statements)
1
32
0
Order By: Relevance
“…Observations of color changes after the Deep Impact encounter in the visible and near IR domains also suggested an increase in small grains and in ice relative to refractory dust in the coma (Knight et al 2007;Schleicher et al 2006). Indeed, remote observations from the Spitzer observatory suggested a very high ice-to-dust ratio of about 10 in the excavated material (which greatly exceeds the gas-to-dust production rate ratio of about 0.5 measured for the background coma), although a ratio in the 1 to 3 range cannot be excluded if a large amount of material fell back to the surface and sublimated (Gicquel et al 2012).…”
Section: Infrared Spectroscopy: Organics and Icy Particlesmentioning
confidence: 98%
“…Observations of color changes after the Deep Impact encounter in the visible and near IR domains also suggested an increase in small grains and in ice relative to refractory dust in the coma (Knight et al 2007;Schleicher et al 2006). Indeed, remote observations from the Spitzer observatory suggested a very high ice-to-dust ratio of about 10 in the excavated material (which greatly exceeds the gas-to-dust production rate ratio of about 0.5 measured for the background coma), although a ratio in the 1 to 3 range cannot be excluded if a large amount of material fell back to the surface and sublimated (Gicquel et al 2012).…”
Section: Infrared Spectroscopy: Organics and Icy Particlesmentioning
confidence: 98%
“…We can crudely calibrate our expectations by considering the dust grain distributions found in rapidly sublimating Solar System comets. For example, the Deep Impact space mission to the comet Temple 1 (A'Hearn et al 2005;Gicquel et al 2012) found maximum particle sizes of b max < 100µm, which safely satisfy this limit. The PR drag timescale we have assumed (Eq.…”
Section: Secular Dimmingmentioning
confidence: 95%
“…In terms of comet activity, and so, in terms of interaction region sizes, Siding Spring can be considered similar to other comets at the time they were visited by previous missions, such as comets 21P/Giacobini‐Zinner, 19P/Borrelly, 81P/Wild, 103P/Hartley2, and 67P/Churyumov‐Gerasimenko (when at its perihelion). On the other hand, Siding Spring was about an order of magnitude more active than comets 26P/Grigg‐Skjellerup, 9P/Tempel1, and comet 67P/Churyumov‐Gerasimenko (before and after perihelion), and an order of magnitude less active than comet P/Halley (e.g., A'Hearn et al, ; Gicquel et al, ; Hansen et al, ; Huddleston et al, ; Johnstone et al, ; Mäkinen et al, ; McFadden et al, ; Meech et al, ). In terms of solar wind and solar radiation factors, each comet is different as the comet interaction with the solar wind strongly depends on the in situ solar activity conditions.…”
Section: Previous Findingsmentioning
confidence: 99%